2018
DOI: 10.1086/694299
|View full text |Cite
|
Sign up to set email alerts
|

Grassroots Participation and Repression under Hu Jintao and Xi Jinping

Abstract: This study examines changes in grassroots participation and repression under the Chinese leaders Hu Jintao and Xi Jinping. Under Xi, the Partystate has launched political campaigns against a range of grassroots activists and organizations. This entails a shift in state repression from fragmentation to consolidation, and it has resulted in less room for contentious participation. However, institutionalized political participation-activities by ordinary people aimed at changing government behavior through offici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…The finding from this chart resonates with those of other studies that have found that the Xi administration has adopted different approaches from the Hu–Wen administration in responding to workers’ collective actions. See, e.g., Fu and Distelhorst 2017; Elfstrom 2019.…”
Section: How Do Local Governments React To Workers’ Collective Actions?mentioning
confidence: 99%
“…The finding from this chart resonates with those of other studies that have found that the Xi administration has adopted different approaches from the Hu–Wen administration in responding to workers’ collective actions. See, e.g., Fu and Distelhorst 2017; Elfstrom 2019.…”
Section: How Do Local Governments React To Workers’ Collective Actions?mentioning
confidence: 99%
“…As Franceschini and Lin's article illustrates, there is a strong demand for rights and fairness among workers (Lee 2007;Ngai 2016). If the existing law and legal design are perceived to be narrow, ineffective, or otherwise not credible to meet the demand of ever-increasing rights awareness, workers, with the assistance of labour NGOs, will bypass existing legal institutions and bring their grievances for extra-legal resolution (Fu and Distelhorst 2018). In accepting the existing political system, as the authors hint, the only viable resolution for labour disputes in China is to re-design the existing labour legal system to legalise workers' right to fair and effective bargaining in formulating their labour contracts.…”
Section: Duality and The Semi-autonomy Of Private Lawmentioning
confidence: 99%
“…Other recent research has focused specifically on the LNGO methodology-that is, how NGOs work, what they do to mobilize workers, and the various ways they perform union-like functions (Chen and Yang 2017;Fu 2018). The third article in this issue, ''Overcoming Collective Action Problems Facing Chinese Workers: Lessons from Four Protests against Walmart'' by Chunyun Li and Mingwei Liu, extends this stream of research through its detailed study of the activities and strategies of LNGOs in strikes against the closures of Walmart stores in China.…”
Section: The Role Of Ngos 2006 To 2015mentioning
confidence: 99%